1984
DOI: 10.1007/bf00163101
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fly ash on microbial C02 evolution from an agricultural soil

Abstract: Unweathered, acidic fly ash from a coal-fired power plant was applied to alfalfa meal-amended agricultural soil at levels equivalent to 0, 100, 400, and 700 tonne ha 1. Amended soils were placed in respirometer jars and monitored for CO2-C evolution over a 37-day period. Fly ash applications of 400 and 700 tonne ha-1 reduced CO2-C production significantly compared to 0 and 100 tonne h a -1 treatments. Carbon dioxide-carbon from all treatments was considerably greater than that from soil treated with 1000 ppm C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

1988
1988
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 6 publications
1
19
0
2
Order By: Relevance
“…Although acidic ash (pH 3.5-5.0) seems to have less of an inhibiting effect on microbial activity than alkaline ash (Pichtel, 1990), inhibitory effects on respiration have still been noted (Arthur et al, 1984;Pichtel, 1990). These effects were attributed to toxic levels of available trace metals which become available at low pH (Arthur et al, 1984).…”
Section: Microbial Activitymentioning
confidence: 97%
“…Although acidic ash (pH 3.5-5.0) seems to have less of an inhibiting effect on microbial activity than alkaline ash (Pichtel, 1990), inhibitory effects on respiration have still been noted (Arthur et al, 1984;Pichtel, 1990). These effects were attributed to toxic levels of available trace metals which become available at low pH (Arthur et al, 1984).…”
Section: Microbial Activitymentioning
confidence: 97%
“…Arthur et al (1984) reported significant reductions in microbial respiration upon fly ash addition in soil to trace metals present at potentially toxic concentrations. The microorganism removal also ceases detoxification of trace elements by enzymatic reductive processes.…”
Section: Introductionmentioning
confidence: 97%
“…Data obtained by Cerevelli, Wong and Pitchel [24][25][26] show that the application of fly ash significantly improves not only the aeration of the soil and the activity of enzymes but enhances also the nitrogen cycle processes in the soil such as nitrification and mineralization. However, Arthur has revealed that excessive application rates of ash (400-700 t/ha) have a negative impact on microbiological activity 27 .…”
Section: Resultsmentioning
confidence: 99%